2004
DOI: 10.2165/00044011-200424010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Tamsulosin on???Lower Urinary Tract Symptoms???Suggestive of Benign???Prostatic Hyperplasia

Abstract: One-year treatment with tamsulosin 0.2 mg/day in Korean patients with suspected BPH was well tolerated and effective in improving LUTS and urinary flow. The effect on symptoms was apparent after 12 weeks of treatment, and symptom improvement was observed for up to 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 20 publications
4
39
0
1
Order By: Relevance
“…The standard dose of tamsulosin for BPH is 0.4 mg (8) but a lower dose (0.2 mg) is also used in Asia (10,11). The conventional Tamsulosin formulation has an absorption profile that is dependent on food intake, and is associated with low levels of intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The standard dose of tamsulosin for BPH is 0.4 mg (8) but a lower dose (0.2 mg) is also used in Asia (10,11). The conventional Tamsulosin formulation has an absorption profile that is dependent on food intake, and is associated with low levels of intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the efficacy of doxazosin, tamsulosin and terazosin in populations (n ¼ 27-205) including Korean, Japanese and Chinese men. [30][31][32][33][34][35] These studies used a dose of 0.2 mg tamsulosin, whereas the CombAT study used 0.4 mg, with no unexpected safety or tolerability issues compared to studies using the 0.2 mg dose. Efficacy of the 5ARI finasteride has also been studied in Asian men, demonstrating reduced prostate volume, and improvement in symptoms and Q max at 6 months and 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…10 Nevertheless, the prevalence of EjD (0.6%-4.5%) and of overall adverse events (6.2%) after 0.2 mg OD tamsulosin in South Korea is considerably lower than in Europe and the United States. 11,12 However, in the studies mentioned above, EjD was not clearly defined or was sometimes reported as retrograde ejaculation. Furthermore, the degree of dysfunction has not been subject to study.…”
Section: Introductionmentioning
confidence: 99%